A panaceia econômico-solidária : uma sistematização dos discursos apologéticos e críticos da economia solidária no Brasil - Dardengo, André Moulin (2013)
The research developed here aims to analyze the theoretical and conceptual discourses for and against the solidarity economy in relation to its function in the logic of accumulation and reproduction of capital. By consulting the literature concerning the solidarity economy produced in Brazil since the mid-1990s, we observe the existence of two major interpretative lines: one that enhances and another that criticizes the present project. There is a demonstration that the authors who favor the solidarity economy argue that it is not functional to capital accumulation and is even emancipatory, playing a kind of discourse already evidenced between the utopian socialists of the early nineteenth century, based on idealistic traits and even a vulgar materialism. While thinkers who criticize solidarity economy, guided by a rigorous Marxist analysis, understand that it does no more than composing strategies of capital accumulation and the way it has been applied, it is sterile as an anti-systemic alternative.